Transcriptional and biochemical responses of monoacylglycerol acyltransferase-mediated oil synthesis and associated senescence-like responses in Nicotiana benthamiana - Divi, Uday K.; El Tahchy, Anna; Vanhercke, Thomas; Petrie, James R.; Robles-Martinez, Jose A.; Singh, Surinder P. (Frontiers in Plant Science, 2014)
Triacylglycerol (TAG) accumulates in plant seeds as a major renewable source of carbon for food, fuel and industrial feedstock. Approaches to enhance TAG content by altering lipid pathways and genes in vegetative parts have gained significant attention for biofuel and other applications. However, consequences of these modifications are not always studied in detail. In an attempt to increase TAG levels in leaves we previously demonstrated that a novel substrate, monoacylglycerol (MAG), can be used for the biosynthesis of diacylglycerol (DAG) and TAG. Transient expression of the Mus musculus monoacylglycerol acyltransferase MGAT1 and 2 in the model plant Nicotiana benthamiana increased TAG levels at 5 days post infiltration (dpi). Here we show that increased TAG and DAG levels can be achieved as early as 2 dpi. In addition, the MGAT1 infiltrated areas showed senescence-like symptoms from 3 dpi onwards. To unravel underlying molecular mechanisms, Illumina deep sequencing was carried out (a) for de-novo assembling and annotation of N. benthamiana leaf transcripts and (b) to characterize MGAT1-responsive transcriptome. We found that MGAT1-responsive genes are involved in several processes including TAG biosynthesis, photosynthesis, cell-wall, cutin, suberin, wax and mucilage biosynthesis, lipid and hormone metabolism. Comparative analysis with transcript profiles from other senescence studies identified characteristic gene expression changes involved in senescence induction. We confirmed that increased TAG and observed senescence-symptoms are due to the MAG depletion caused by MGAT1 activity and suggest a mechanism for MGAT1 induced TAG increase and senescence-like symptoms. The data generated will serve as a valuable resource for oil and senescence related studies and for future N. benthamiana transcriptome studies.